„622 upadki” Witkacego w listach do żony o żonach - Narewska, Dorota (Dydaktyka Polonistyczna, 2020)
The article is a view of relation that bonds Stanislaw Ignacy Witkiewicz and Jadwiga Unrug- -Witkiewicz that emerges from his mails to the wife. His view of imperfect relationship of man and woman, marriage, a relation towards the sacrament, offspring, love and faithfulness contains the traces of God’s reality.